Mycotoxin Binders Effect on Ovaries of Pregnant Mice Exposed to Zearalenone - Ragil Angga Prastiya; Abdul Samik; Amung Logam Saputro (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Mycotoxin, a secondary metabolite produced by mushroom, has proven to cause various cytotoxic effects to animals. Zearalenone is one type of mycotoxin which is produced by Fusarium graminearum mushroom and has a cytotoxic effect to the reproduction system and cattle productivity by inducing apoptosis in the animal's ovaries, uterus, and placenta. This research tested the potentials of mycotoxin binders in eliminating the effect of zearalenone which can be seen from the expression of caspase 3, the content of malondialdehyde (MDA), and the quantity of corpus luteum in the ovaries of pregnant mice (Mus musculus). Twenty mice were grouped into five different treatments, namely K+ (not exposed to zearalenone and mycotoxin binders), K- (0.1 mg/mouse/day of zearalenone dosage), P1 (0.1 mg/mouse/day of zearalenone dosage and 0.5 mg/mouse/day of mycotoxin binder dosage), P2 (0.1 mg/mouse/day of zearalenone dosage and 1 mg/mouse/day of mycotoxin binders), and P3 (0.1 mg/mouse/day of zearalenone and 2 mg/mouse/day of mycotoxin binders), with 10-days treatment time. The results showed that the potentials of mycotoxin binders could be found on the gradual decline in the expression of caspase 3 in P1, P2 and P3 compared to that in K- (negative control). The results also showed a significant difference in the content of malondialdehyde (MDA) in K- compared to that in K+, P1, P2, and P3. Meanwhile, the quantity of corpus luteum in K- was also starkly different to that in K+, P1, P2, and P3. It can then be concluded that mycotoxin binders are very effective in eliminating the exposure of zearalenone.